3-Pyridin-2-yl-1H-1,2,4-triazol-5-amine - Dolzhenko, Anton V. (International Union of Crystallography, 2008)
In the title compound, C(7)H(7)N(5), the non-H atoms are almost coplanar (r.m.s. deviation = 0.050 Å), with the N atom of pyridine ring oriented to the N—N(H) side of the 1,2,4-triazole ring. The mean planes of the pyridine and 1,2,4-triazole rings form a dihedral angle of 5.58 (7)°. The N atom of the amino group adopts a pyramidal configuration. The molecules are linked into a two-dimensional network parallel to (10[Image: see text]) by N—H⋯N hydrogen bonds.